Enhancing Students’ English Vocabulary through the Help of Track Star Online Program - Irham, Novia Robeitah; Rahmah , Isnayni; Daulay, Sholihatul Hamidah (UICELL, 2023)
Vocabulary is a basic for how well students learn, speak, listen, read, and write a language. One of the English learning strategies used to motivate students in learning vocabulary is through both offline and online media. One of the online media that can be applied in learning vocabulary is the Track Star online program. Researchers are interested in conducting research with the help of the Track Star online program, so that it aims to increase students' English vocabulary. The method used was Classroom Action Research, this research was conducted in 2 cycles, in cycle I, mean score was 70.5 with the percentage of passing KKM being 35%. In cycle II, the mean score was 83 with the percentage of KKM passing is 85%, the success rate of Classroom Action Research (CAR), which was above 24% of students who could pass the KKM. The Classroom Action Research (CAR) is a success by default, and the cycle can be broken. From the result, it can be concluded that Track Star online program is a fun and effective way to enhance students’ English vocabulary. Keywords: Vocabulary, Track Star online program, offline and online media